Antiviral effect of high-dose ivermectin in adults with COVID-19: A proof-of-concept randomized trial - Krolewiecki, Alejandro Javier (2021)
Background: There are limited antiviral options for the treatment of patients with COVID-19. Ivermectin (IVM), a macrocyclic lactone with a wide anti-parasitary spectrum, has shown potent activity against SARSCoV-2 in vitro. This study aimed at assessing the antiviral effect of IVM on viral load of respiratory secretions and its relationship with drug concentrations in plasma. Methods: Proof-of-concept, pilot, randomized, controlled, outcome-assessor blinded trial to evaluate antiviral activity of high-dose IVM in 45 COVID-19 hospitalized patients randomized in a 2:1 ratio to standard of care plus oral IVM at 0¢6 mg/kg/day for 5 days versus standard of care in 4 hospitals in Argentina. Eligible patients were adults with RT-PCR confirmed SARS-CoV-2 infection within 5 days of symptoms onset. The primary endpoint was the difference in viral load in respiratory secretions between baseline and day-5, by quantitative RT-PCR. Concentrations of IVM in plasma were measured. Study registered at ClinicalTrials.gov: NCT04381884. Findings: 45 participants were recruited (30 to IVM and 15 controls) between May 18 and September 9, 2020. There was no difference in viral load reduction between groups but a significant difference was found in patients with higher median plasma IVM levels (72% IQR 59 77) versus untreated controls (42% IQR 31 73) (p = 0¢004). Mean ivermectin plasma concentration levels correlated with viral decay rate (r: 0¢47, p = 0¢02). Adverse events were similar between groups. No differences in clinical evolution at day-7 and day-30 between groups were observed. Interpretation: A concentration dependent antiviral activity of oral high-dose IVM was identified at a dosing regimen that was well tolerated. Large trials with clinical endpoints are necessary to determine the clinical utility of IVM in COVID-19.